Application Method of Smart Dynamic DNS in Huge e-Commerce - Zhiwei Shen; Bingyi Fang (Dianxin kexue)
As the scale of e-Commerce users and individual demand is increasing, the existing framework of e-Commerce has been unable to provide users with a complete solution. First the e-Commerce network architecture was put forward, and a detailed discussion was made on each part of the network architecture, a kind of smart dynamic domain name system and the optimal routing method of user access of e-Commerce were designed, at last the user access to electronic commerce exchange process was given.